By the light of the halloween moon - Stutson, Caroline; Hawkes, Kevin (New York : Lothrop, Lee & Shepard Books, 1993)
In this cumulative story, a cat's pursuit of a toe sets off a chain of events.
Keywords: Halloween -- Fiction